Perlombaan Senam Kreasi Antar Mahasiswa Pendidikan Jasmani Kesehatan dan Rekreasi Universitas Rokania Kabupaten Rokan Hulu - -, Siska; Indah, Debby; Bakri, Zamhar; -, Suhermon; -, Tofikin; Hendryanto, Ferri; -, Arisman; Pratiwi, Rati (JURNAL MASYARAKAT NEGERI ROKANIA, 2024)
The creative gymnastics competition is an activity organized by the Physical Education, Health and Recreation (PJKR) Study Program at Rokania University as an effort to increase creativity, physical fitness and teamwork. This event aims 1. To provide opportunities for students to develop gymnastics skills, express creativity, and increase their understanding of the importance of sport in everyday life by displaying creative gymnastics movements combined with elements of art and culture. 2. To analyze the implementation, impact and benefits obtained from creative gymnastics competitions, both in terms of physical health and the development of participants' soft skills. The venue was the Putra Rokania Hall, the competition which was attended by students from the Physical Education, Health and Recreation Study Program at Rokania University consisted of 9 groups. The results obtained from the creative gymnastics competition at the PJKR Study Program at Rokania University are 1st Place in the Sueq Group (Tio, Nabila and Fauzan) 2nd Place in Bolu Composite (Bowo and Lulu) 3. 3rd Place in the Deadly Duo Group (Ratih and Fatia)